Aplicación de Proceso de Enfermería en paciente adulto mayor con Diabetes Mellitus Tipo II, en el Hospital General Guasmo Sur - Carpio León, Viviana Alexandra (2019)
Diabetes mellitus is considered a chronic disease that appears when the pancreas does not produce enough insulin or when the body does not properly use the insulin it produces. The clinical case study is about a 72-year-old patient admitted to the General Guasmo Sur Hospital in the city of Guayaquil with a medical diagnosis of Type 2 Diabetes Mellitus, presenting polydipsia, polyuria, fatigue, etc. When making the assessment during the interrogation in the personal history, he refers to having a Hip Fracture surgery and in the family history he refers to having a daughter with Obesity. The doctor refers to perform a hemoglucotest and other laboratory tests, which was obtained as a result of Diabetes mellitus type II, which is applied nurse diagnosis of Disposition to improve nutrition, then the correct pharmacological and non-pharmacological treatment is initiated; which educates the patient and his relatives of how this disease should be treated, the diet that should follow, physical activity. The patient went to all his consultations, then an improvement could be observed since he followed all the treatment explained and has not presented complications in the course of time.